Characterization of a flat-panel detector for ion beam spot measurements - Martišíková, Mária; Breithaupt, Bernadette; Brons, Stephan; Ackermann, Benjamin; Jäkel, Oliver (Physics in medicine and biology, 2012)
Dynamic beam delivery techniques are being increasingly used for cancer therapy. Scanning ion beams require extensive and time-demanding quality assurance procedures and beam tuning. Accordingly, fast measurement techniques improving the efficiency of the procedures and accommodating the safety requirements are highly desirable. Major requirements for a detector used for beam-shape measurements are high spatial resolution in two dimensions, reusability, online readout and easy handling. At the Heidelberg Ion Beam Therapy Facility (Germany), we examined the performance of the RID 256 L flat-panel detector for beam spot measurements. The two-dimensional beam profiles of proton and carbon ion beams measured were compared to measurements with radiographic films at intermediate energies using the Γ index. The difference to the beam width measured with radiographic films of less than 3% demonstrates sufficient accuracy of ion beam width measurements possible with this detector for both proton and carbon ion beams. The beam shapes were also measured at different beam intensities. At both the highest and lowest energies available at the HIT, no beam spot-shape deformation was found with increasing beam intensities, as long as the boundary of the dynamic range was not exceeded. The signal leak along the readout direction was identified as an undesirable effect. However, due to small amplitudes and static beams, this effect is of minor importance for beam spot measurements. Distortion of results due to detector radiation damage was monitored. No detector radiation damage was observed over the experiments. Moreover, the observed short-time detector response stability (within ±0.1%) as well as medium term stability (within 0.5% in 15 months) was excellent. This flat-panel detector is compact and easy to use. Together with its low weight, this helps to speed up measurement procedures substantially. All these properties make this an ideal detector for the fast, high-resolution imaging of static ion beam spots needed for constancy measurements in daily beam quality assurance and for accelerator tuning. For daily use, radiation damage has to be monitored continuously and corrected for if necessary.